ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR TINGKAT KESEHATAN KEUANGAN KSP DUTA SEJAHTERA PERIODE 2022–2025 - Khairani Alawiyah Matondang; Muhammad Abdi; Fahmi Apriyansyah Siregar; Runggu Sihombing (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The primary focus of this study is to evaluate the financial health of KSP Duta Sejahtera during the 2022–2025 period in accordance with Minister of Cooperatives and Small and Medium Enterprises Regulation No. 14/Per/M.KUKM/XII/2009. This study employs a quantitative descriptive method with a case study approach on KSP Duta Sejahtera for the years 2022–2025 based on Ministerial Regulation No. 14/Per/M.KUKM/XII/2009. The data used consists of the cooperative’s financial statements obtained from the cooperative’s official website and analyzed through seven aspects of cooperative health assessment: capital, quality of productive assets, management, efficiency, liquidity, independence and growth, and the cooperative’s identity. The analysis results show that KSP Duta Sejahtera achieved an average health score of 71.81, earning the rating “Fairly Healthy.” The aspects of capital, management, quality of productive assets, and cooperative identity are in good condition, while the aspects of efficiency, liquidity, and self-reliance and growth still need improvement so that the cooperative’s health level can advance to the “healthy” category.